STUDY OF BREAST SECRETIONS - Aviño, J. (2015)
200 patients affected nipple discharge is studied, analyzing the results obtained with different methods and techniques in breast disease diagnostic mammography, telethermography, thermography plate, cytology and pathology study. Galactography value in the study of ductal pathology is highlighted. From an etiological point of view, the iatrogenic occupied an important place. The benign (papillomas and ductal ectasia) was largely responsible for the abnormal nipple discharge.